2014
DOI: 10.5114/fn.2014.45565
|View full text |Cite
|
Sign up to set email alerts
|

Original article Proliferation index revisited in neuroblastic tumors

Abstract: A b s t r a c t Neuroblastic tumors (NB) are the most common extracranial pediatric neural crest-derived tumors, with a dismal outcome in a substantial

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…In an in vitro study, the expression levels of Topo‐IIα were found to be closely related to tumor cell proliferation and aggression . The relationship of expression of Topo‐II and Ki‐67 has also been reported in malignant tumors …”
Section: Introductionmentioning
confidence: 89%
“…In an in vitro study, the expression levels of Topo‐IIα were found to be closely related to tumor cell proliferation and aggression . The relationship of expression of Topo‐II and Ki‐67 has also been reported in malignant tumors …”
Section: Introductionmentioning
confidence: 89%
“…The pathological aspects of GNTs remain unclear however, case reports have found Olig2 commonly expressed in these tumors and thus lean more toward oligodendrogliomas. Three subtypes of GNTs that demonstrate Olig2 upregulation are dysembryoplastic neuroepithelial tumors (DNTs; Komori and Arai, 2013 ; Matsumura et al, 2013 ), papillary glioneuronal tumors (PGNTs; Tanaka et al, 2005 ; Chen et al, 2006 ; Gelpi et al, 2007 ; Iżycka-Świeszewska et al, 2008 ; Matsumura et al, 2013 ), and rosette-forming glioneuronal tumors ( Wang et al, 2009 ; Luan et al, 2010 ; Xiong et al, 2012 ; Matsumura et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Olig2 expressing cells were also found in PGNTs suggesting that these tumors may be oligodendroglial or oligodendroglial-like. Histologically, PGNTs exhibit two distinct architectures: (1) pseudopapillary structures surrounded by (2) compact regions consisting of neuronal elements under different maturation stages ( Tanaka et al, 2005 ; Gelpi et al, 2007 ; Iżycka-Świeszewska et al, 2008 ; Marumo et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%